SURVEI KETERAMPILAN PASSING BAWAH BOLA VOLI DI DALAM PEMBELAJARAN PENJAS PADA SISWA KELAS VII DI SMP NEGERI 34 SELUMA - Andriansyah; Hajri Aprizal; Mesterjon (Journal of Education and Culture (JEC), 2022)
This study aims to determine the Volleyball Bottom Passing Skills Survey in Physical Education Learning for 30 male and female students in Class VII at SMP Negeri 34 Seluma. This research is quantitative descriptive. The method used is a survey. The population of this study were students at SMP Negeri 34 Seluma Kec. Semidang Alas, totaling 30 students. Data collection techniques using tests, obtained the results of Volleyball Underpass Skills which were mostly in the Very Good category by 7 male students with a percentage of 46.6% while in the Good category by 6 male students and 6 female students with a percentage of 40%. . Whereas for the moderate category there are 3 female students with a percentage of 20% and for male students with a percentage of 13.4% while in the less category there is 1 female student with a percentage of 6.6% for the less category it is 0%.